Malawi Urbanization Review : Leveraging Urbanization for National Growth and Development - World Bank (World Bank, Washington, DC, 2016)
The Malawi Urbanization Review aims to provide fresh perspectives on urbanization in Malawi, by analyzing the current and potential contribution of urbanization to long-term national development and the current institutional and financial capacity of local governments to manage the process. Analyses presented in this report are particularly timely as Malawi is planning for the coming half decade through the Malawi Growth and Development Strategy (MGDS) III (2016-2020). Malawi is urbanizing at a moderate rate and has a good chance of proactively managing the urbanization process. Opportunities may arise from a positive structural change that Malawi’s economy is undergoing, whereby the driver of growth and job creation moves from agriculture to non-agricultural sectors. Faster urbanization, with strong linkages with rural areas, can contribute further to deepening such structural change. To unlock the potential of urbanization as a catalyst for long-term economic development, it is necessary to strengthen the capacity of urban local governments to generate revenues and meet the key infrastructure and service needs in urban areas, which remain challenging even at the current rate of urbanization.